Remote Walker breakdown and coupling breaking in parallel nanowire systems - Krishnia, S. (2014)
In a multiple nanowire system, we show by micromagnetic simulations that a transverse domain wall in a current-free nanowire can undergo a remote Walker breakdown when it is coupled to a nearby current-driven domain wall. Moreover, for chirality combination with the highest coupling strength, the remote Walker breakdown preceded the current-induced Walker breakdown. The Walker breakdown limit of such coupled systems has also been shifted towards higher current densities, where beyond these, the coupling is shown to be broken.